1977
DOI: 10.1149/1.2133234
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Containing Raney Nickel Catalyst for Hydrogen Electrodes in Alkaline Fuel Cell Systems

Abstract: In alkaline hydrogen-oxygen fuel cells Raney nickel is employed as catalyst for hydrogen electrodes. The rate of anodic hydrogen conversion has been increased significantly by using a titanium-containing Raney nickel. The properties of the catalyst powder, the influence of particle diameter, and the behavior of electrodes under load are described. Impedance measurements have been used to characterize the electrodes. In fuel cell systems the supported electrodes are normally operated at current densities up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 6 publications
2
35
2
1
Order By: Relevance
“…The findings presented here are contrary to those of both Mund et al [17] and Gros et al [20] NiAl is a B2 cubic phase with a wide compositional stability field extending from 42 -69 at.% Ni. On the Al-rich side, the deviation from stoichiometry is accommodated by the inclusion of vacancies on the Ni lattice sites [20], with the number of unoccupied Ni-sites approaching one third as the Ni 2 Al 3 stoichiometry is approached.…”
Section: Discussion and Analysiscontrasting
confidence: 99%
See 4 more Smart Citations
“…The findings presented here are contrary to those of both Mund et al [17] and Gros et al [20] NiAl is a B2 cubic phase with a wide compositional stability field extending from 42 -69 at.% Ni. On the Al-rich side, the deviation from stoichiometry is accommodated by the inclusion of vacancies on the Ni lattice sites [20], with the number of unoccupied Ni-sites approaching one third as the Ni 2 Al 3 stoichiometry is approached.…”
Section: Discussion and Analysiscontrasting
confidence: 99%
“…Mund et al [17] found that Ti can substitute for Ni in both the Ni 2 Al 3 and NiAl 3 phases, although the formation of the additional phase TiAl 3 has also been observed [19]. Based on a study of melt spun ribbons of Ti-doped Raney Ni, Gros et al [20] reported the formation of dendritic morphologies in the as-solidified material, these structures being similar to those observed in undoped Raney-type Ni.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations